Perkembangan Kemampuan Penalaran Matematis Siswa Selama Diterapkan Pembelajaran Think Pair Square - Afri, Lisa Dwi; Utami, Nita Putri (Math Educa Journal, 2018)
Students' mathematical reasoning ability will be better and develop if the teacher provides learning that supports these abilities. However, most of the students of class XI Science at SMAN 2 Painan have not used and developed their mathematical reasoning abilities optimally, this is due to teachercentered learning. The purpose of this study was to determine the development of mathematical reasoning skills in class XI science students of SMAN 2 Painan during Think Pair Square learning. This research is a descriptive research. The research instrument is a quiz. Quiz is analyzed by determining the average quiz for each meeting, students who complete based on the KKM and determine the performance criteria achieved by students based on the assessment of Iryanti's performance. The results show that students' mathematical reasoning abilities develop.Keywords: Think Pair Square,Mathematical Reasoning Abilities